The Nature of Electromagnetic Interference - Levitt, Harry (Journal of the American Academy of Audiology, 2001)
This report provides a brief tutorial on the underlying physical forces that lead to interference with hearing aids and assistive listening devices, as well as measurement issues and possible solutions to the problem.Abbreviations: ALD = assistive listening device, EM = electromagnetic, TEM = transverse electromagnetic
Keywords: Assistive listening device; hearing aid; interference